Fabric‐hydrogel composite membranes for culturing microalgae in semipermeable membrane‐based photobioreactors. Issue 1 (28th July 2015) - Lee, Seung‐Yong; Kim, Z‐Hun; Oh, Hwa Yeon; Choi, Younghoon; Park, Hanwool; Jung, Daewoo; Kim, Jong‐Min; Na, Yang Ho; Lim, Sang‐Min; Lee, Choul‐Gyun; Lee, Jin‐Kyun
ABSTRACT: In this article, we demonstrate that hydrogel‐based composite membranes are used as semipermeable materials for the construction of photobioreactors (PBRs). PBRs are developed to culture microalgae using nutrients dissolved in seawater, and thus they need to be fabricated with membranes possessing sufficient material‐transport properties. While hydrogels are characterized by their highly swelling nature in water and therefore have desirable transport of dissolved matter, they lack the mechanical strength to be cast into thin structures of large surface area. This issue motivated us to design a new concept, i.e., fabric‐hydrogel composite membranes (FHCM s). A cotton fabric inside the hydrogel matrix endows the composite with tensile strength, which enables casting ofFHCM s into thin membranes. SeveralFHCM s were prepared with 2‐hydroxyethyl methacrylate (HEMA ), cross‐linking poly(ethylene glycol) dimethacrylate (PEGDMA ) and a sheet of gauze by controlling the composition of the monomers and water. In the permeability measurement of nitrate ions, a key ingredient for the growth of microalgae, the permeability coefficient reached as high as 1.2 x 10 −8 m 2 min −1, which is roughly three times higher than that of a commercially available semipermeable membrane (3.3 x 10 −9 m 2 min −1 ). In the following evaluation of microalgal culture, a PBR constructed with aFHCM was able to maintain sufficient NO 3 − ion concentration and pH of the culture broth, supporting microalgal growth. These results suggest that the composite membranes with hydrogel and fabric have potential in the application of microalgal culture for bio‐diesel production in a marine environment. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 108–114 Abstract : Fabric‐hydrogel composite membranes (FHCMs) are proposed as semipermeable materials for the construction of photobioreactors. A cotton fabric inside the hydrogel matrix endows the composite with tensile strength, which enables casting of FHCMs into thin membranes. In permeability coefficient measurements of NO − 3 ions, it reached as high as 1.2 × 10 −8 m 2 min −1 . In microalgal culture, a photobioreactor with a FHCM could maintain sufficient NO − 3 ion concentration and pH of the culture broth, supporting microalgal growth.